Perspective: Plant-Based Meat Alternatives Can Help Facilitate and Maintain a Lower Animal to Plant Protein Intake Ratio - Messina, Mark; Duncan, Alison M.; Glenn, Andrea J.; Mariotti, Francois (Advances in nutrition (Bethesda, Md.), 2023)
The health and environmental advantages of plant-predominant diets will likely lead to increasing numbers of consumers reducing their reliance on animal products. Consequently, health organizations and professionals will need to provide guidance on how best to make this change. In many developed countries, nearly twice as much protein is derived from animal versus plant sources. Potential benefits could result from consuming a higher share of plant protein. Advice to consume equal amounts from each source is more likely to be embraced than advice to eschew all or most animal products. However, much of the plant protein currently consumed comes from refined grains, which is unlikely to provide the benefits associated with plant-predominant diets. In contrast, legumes provide ample amounts of protein as well other components such as fiber, resistant starch, and polyphenolics, which are collectively thought to exert health benefits. But despite their many accolades and endorsement by the nutrition community, legumes make a negligible contribution to global protein intake, especially in developed countries. Furthermore, evidence suggests the consumption of cooked legumes will not substantially increase over the next several decades. We argue here that plant-based meat alternatives (PBMAs) made from legumes are a viable alternative, or a complement, to consuming legumes in the traditional manner. These products may be accepted by meat eaters because they can emulate the orosensory properties and functionality of the foods they are intended to replace. PBMAs can be both transition foods and maintenance foods in that they can facilitate the transition to a plant-predominant diet and make it easier to maintain. PBMAs also have a distinct advantage of being able to be fortified with shortfall nutrients in plant-predominant diets. Whether existing PBMAs provide similar health benefits as whole legumes, or can be formulated to do so, remains to be established.